Work-family conflict and time use: psychometric assessment of an instrument in ELSA-Brazil - Karina Araujo Pinto; Greice Maria de Souza Menezes; Rosane Härter Griep; Keury Thaisana Rodrigues dos Santos Lima; Maria da Conceição Almeida; Estela M L Aquino (Universidade de São Paulo, 2016)
ABSTRACT In this study, we evaluated the psychometric properties of the items to measure the work-family conflict and the time use for personal care and leisure, included in the baseline questionnaire of the Longitudinal Study of Adult Health (ELSA-Brazil). We evaluated temporal stability (7-14 days) using kappa statistic and the validity of the construct by the correlation of Kendall's tau with other variables. Test-retest stability was discreet to moderate and the correlations were compatible with the underlying theory. Future studies in the context of ELSA-Brazil and in other populations will complement the assessment of its relevance.